Development And Evaluation of A Sufi Oriented Experiential Learning Model In Islamic Religious Education - Suharjo; Duski Samad; Ulfatmi Amirsyah; Samsul Nizar (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study addressed the low emotional-spiritual intelligence among students at SMAN 1 Kinali, a problem stemming from a conventional Islamic Religious Education (PAI) approach overly focused on cognitive and dogmatic instruction. The research aimed to develop, implement, and evaluate the validity, practicality, and effectiveness of a Sufi-oriented experiential learning model that integrates Al-Ghazali’s spiritual stages (maqamat) with Kolb’s experiential learning cycle. Employing a Research and Development (R&D) design using the 4D model (Define, Design, Develop, Disseminate), data were collected through mixed methods, including pre-test/post-test ESQ scales, participant observation, reflective journals, and in-depth interviews. The experimental group (n=32) underwent the intervention, while a control group (n=30) received conventional instruction. Quantitative data analysis using paired and independent sample t-tests revealed a significantly higher ESQ improvement in the experimental group (mean gain = +27.52, p < 0.01, d = 3.78) compared to the control group (mean gain = +10.09). Qualitative thematic analysis showed students' progression to the initial taubah (repentance) stage, marked by heightened self-awareness, behavioral changes, and value internalization. The findings conclude that the developed model is valid, practical, and effective in enhancing students' ESQ. This study offers a replicable pedagogical framework for holistic PAI, emphasizing the integration of spiritual psychology and experiential pedagogy.